1986
DOI: 10.1108/eb008181
|View full text |Cite
|
Sign up to set email alerts
|

The Fashion‐conscious Elderly: A Viable, but Neglected Market Segment

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 0 publications
2
28
0
Order By: Relevance
“…This is supported by Silvers (1997), who found that the lives of people in their 50s are in a constant state of flux, and actually change more than those of people in their 20s. Additionally, Sudbury and Simcock (2009) asserted that treating the over 50s as one segment may result in crucial findings being overlooked within this important segment (Greco, 1986) because older consumers become more dissimilar in terms of lifestyles, needs and consumption habits as they age (Moschis, 1996) due to the different life-changing events they experience, such as the death of a partner or a divorce, along with differences in how they age physiologically, socially and psychologically (Moschis, 2003).…”
Section: Older Adultsmentioning
confidence: 98%
“…This is supported by Silvers (1997), who found that the lives of people in their 50s are in a constant state of flux, and actually change more than those of people in their 20s. Additionally, Sudbury and Simcock (2009) asserted that treating the over 50s as one segment may result in crucial findings being overlooked within this important segment (Greco, 1986) because older consumers become more dissimilar in terms of lifestyles, needs and consumption habits as they age (Moschis, 1996) due to the different life-changing events they experience, such as the death of a partner or a divorce, along with differences in how they age physiologically, socially and psychologically (Moschis, 2003).…”
Section: Older Adultsmentioning
confidence: 98%
“…The socio-psychological meaning associated with fashion clothing is more important in its adoption than its functional attributes. 40 Psychographics are important in the purchase of fashion products 41,42 and fashion clothing consumption. 43 …”
Section: Gender Age and Fashion Clothing Involvementmentioning
confidence: 99%
“…Our preoccupation with the traditional family has allowed us to drift far a field from current demographic realities. Regularly we fault existent consumer behavior literature for oversights such as not considering differing consumer behavior of singles (Ezell and Russell, 1985;Stern et al, 1987;Shipp, 1988) or the heterogeneity of older consumers (Greco, 1986;Schewe, 1988;Sorce et al, 1989). Less regularly do consumer behavior researchers note the need for a better understanding of the consumer behavior of the indigent, poor, and homeless (some notable exceptions include the work of Sexton, 1974;Andreasen, 1986;Hill and Stamey, 1990;Hill, 2001).…”
Section: Generating Research Questionsmentioning
confidence: 92%